An Analysis of Factors Influencing Repurchase Intention in the Automotive Sector in Batam City - Nurjanah, Listia; Alexsandro, Wiko (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The use of social media continues to increase, followed by increasingly prohibitions on entrepreneurs using this media to market their business. On the other hand, this results in increasingly fierce competition, where marketers need to pay attention to effective marketing strategies to encourage special features or characteristics that can make consumers interested in buying products in their stores, as well as to maintain consumer loyalty. This research aims to analyze the influence of social media content, website content on repurchase intentions through E-WOM mediation and interactivity on students in choosing coffee drinks. The research approach used is quantitative. Data collection was obtained through distributing surveys to 300 research respondents of college students in Batam City. Data were analyzed using SMART-PLS software to carry out descriptive statistical analysis, structural Equation Modeling (SEM) analysis, and hypothesis testing to test the truth of the research hypothesis. The research findings concluded that social media content and website content play a significant role in influencing E-WOM as both show statistically significant effects. Furthermore, only social media content has a significant influence on interactivity, while website content does not demonstrate a notable impact on this variable. In addition, both E-WOM and interactivity significantly affect repurchase intention. E-WOM is found to significantly mediate the relationship between both social media content and website content on repurchase intention. On the other hand, interactivity mediates the relationship between social media content and repurchase intention